ESTABLISHMENT OF LOCAL DIAGNOSTIC REFERENCE LEVELS (LDRL) FOR ADULT CHEST COMPUTED TOMOGRAPHY EXAMINATION IN A SOUTH-EASTERN STATE OF NIGERIA (Journal of Biomedical Investigation, 2023)
Background: Diagnostic reference levels (DRLs) are indispensable tools and a sub-principle in optimization of radiation dose in the field of Radiography and radiological sciences. It is intended to identify and reduce unnecessary high ionizing radiation dose to patients during radiological examinations such as Chest Computed Tomography (CT) examination.Objective: To determine local Chest Computed Tomography dose index (CTDIvol) and Dose length product (DLP) in the selected CT centers, estimate the Effective dose (ED) for Chest CT examination and compare our results with both stated Nigerian national and international standards.Materials and Methods: A total of 240 adult subjects referred for chest CT examination from the four considered CT radiodiagnostic centers were surveyed within a period of six months. Data were obtained from different models of CT scanners which included Toshiba Alexium, Brightspeed multidetector CT scanner and Siemens Somerton respectively. Radiation dose were generated from Computed Tomography Dose Index (CTDIvol) and Dose Length Product (DLP) from where the effective dose (E) was calculated using the product of chest DLP and the normalized coefficient found in the European guideline. Data were analyzed using SPSS version 20 Chicago software. The mean values for each CT centre were calculated at 75th percentile of DLP and CTDIvol chosen as the basis for DRLs.Results: The 75th percentile of CTDIvol and DLP were 22 mGy and 800 mGy.cm. The effective dose was 13. 6mSv.Conclusion: Radiation dose variations across the four CT centres surveyed have revealed the need for urgent dose optimization to narrow down centre-specific and composite DRL values to national and international best practice.
Keywords: Computed Tomography; Diagnostic Reference levels; Dose Optimization; Effective dose